Features of facies of reefs of the silurian age of Volyn-Podillia - T. V. Sushko (Ukrainian State Geological Research Institute (UkrSGRI), 2021)
On the territory of Volyn-Podillya Silurian deposits are represented by thick strata of terrigenous and carbonate deposits, they are mainly represented by marls, argillites, limestones, dolomites, etc. Because these deposits have excellent reservoir properties, they are promising for hydrocarbons, and clays serve as oil and gas trap covers. In industry, they are often used as a building material. Industrial accumulations of hydrocarbons in the carbonate strata of Volyn-Podillya have not yet been identified. However, there are numerous signs of oil and gas potential of these deposits in the Silurian and Upper Devonian limestones. In the carbonate strata of the Silurian age there are oil and gas-prospecting reef limestones in three horizons: Skal, Malynovets and Bahovytsia. They form a barrier reef that stretches from the area of Lokachynsky Val in the northwest to the city of Chernivtsi in the southeast. Some samples of the core raised from rifogenic rocks of Silurian had an oil smell, smears and inclusion of liquid oil in cracks and cavities. Sometimes whole intervals of cavernous dolomites were impregnated with light oil. During the re-drilling of rifogenic rocks, stratification of drilling mud and oil film was recorded. In the process of testing limestones of the rock horizon in W. 12-Lokachi received a small influx of oil, and in W. 1-Volodymyrivska, a gas inflow with a flow rate of 1.4 thousand m³/day was obtained from the rocks of the Bahovytsia horizon. From Malinovetsky (W. 10, 15, 17-Lokachi) and Bagovytsky (W. 15-Lokachi) horizons, inflows of formation water with a significant amount of dissolved gas (96 % methane) and oil films were obtained. Therefore, these data indicate the prospects of exploration of hydrocarbon deposits in the riphogenic carbonate strata of the Silurian age of Volyn-Podillya and their thorough study. The main task of this article is: to determine the distribution of reef facies of the Silurian Volyn-Podillya and horizons in these deposits. Clarify their stratigraphic affiliation. Show the role of tectonic movements on the formation of facies and the thickness of reef deposits, as well as the possibility of searching for hydrocarbons in Silurian reef formations.